Additive estimates for discrete Hardy-type operators - Kalybay, Aigerim; Shalginbayeva, Saltanat (Eurasian Mathematical Journal, 2018)
We establish necessary and sufficient conditions for the validity of weighted additive estimates of the norms of the discrete Hardy operators.